Screening for antifungal activity in plants from central Argentina - Palacios, Sara Maria (2010)
Ethanolic extracts from aerial parts of 71 native plants from Argentina were tested by bioautography on Thin Layer Chromatography (TLC) for their antifungal effects against pathogenic Fusarium verticillioides. The extracts of Aristolochia argentina (Aristolochiaceae), Flourensia oolepis (Asteraceae), Gaillardia megapotamica (Asteraceae), Salvia cuspidata (Lamiaceae) and Trichocline reptans (Asteraceae) at Minimum Inhibitory Concentrations (MICs) of 0.03 to 0.12 mg/spot were highly effective in inhibiting the fungal growth followed by extracts from Baccharis artemisioides (Asteraceae), Baccharis salicifolia (Asteraceae), Dalea elegans (Fabaceae), Heterothalamus alienus (Asteraceae), Lepechinia floribunda (Lamiaceae), Vernonia nudiflora (Asteraceae) and Zanthoxylum coco (Rutaceae) at MICs of 0.25 - 0.50 mg/spot. While, F. oolepis, T. reptans and A. argentina extracts proved most potent, with MICs of 0.03, 0.03 and 0.06 mg/spot, respectively. Further studies are required with extracts of the most active species in bioguided assay isolation to obtain new molecules with potent antifungal properties to control harmful fungi such as F. verticillioides.